Analisis Pembelajaran Teori Behavioristik Siswa dalam Pembelajaran IPA berbasis Kontekstual dalam Meningkatkan Semangat Belajar Siswa Kelas 4 Sekolah Dasar - Mahayani, Luh Pt Oka; Suarni, Ni Ketut; Margunayasa, I Gede (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This research aims to evaluate the impact of applying Behavioristic theory in the context of Natural Sciences (Science) learning in grade 4 elementary schools, with a focus on increasing the effectiveness of contextual-based learning. Data analysis involves the variables of student participation, understanding of science concepts, and level of enthusiasm for learning. The results showed that there were significant variations between the experimental group and the control group.